Detailed Analysis of SCARA-Type Serial Manipulator on a Moving Base with LabView. (8th April 2013) - Kaleli, Alirıza; Dumlu, Ahmet; Çorapsız, M. Fatih; Erentürk, Köksal
Robotic manipulators on a moving base are used in many industrial and transportation applications. In this study, the modelling of a RRP SCARA-type serial manipulator on a moving base is presented. A Lagrange-Euler approach is used to obtain the complete dynamic model of the moving-base manipulator. Hence, the dynamic model of the manipulator and the mobile base are expressed separately. In addition, Virtual Instrumentation (VI) is developed for kinematics, dynamics simulation and animation of the manipulator combined with the moving-base system. Using the designed VI in LabView, the relationship between frequency of disturbances of the moving base and joint torques is investigated. The obtained results are presented in graphs.